Targeting USP7-Mediated Deubiquitination of MDM2/MDMX-p53 Pathway for Cancer Therapy: Are We There Yet? - Qi, Si-Min; Cheng, Gang; Cheng, Xiang-Dong; Xu, Zhiyuan; Xu, Beihua; Zhang, Wei-Dong; Qin, Jiang-Jiang (Frontiers in Cell and Developmental Biology, 2020)
The p53 tumor suppressor protein and its major negative regulators MDM2 and MDMX oncoproteins form the MDM2/MDMX-p53 circuitry, which plays critical roles in regulating cancer cell growth, proliferation, cell cycle progression, apoptosis, senescence, and angiogenesis. Recent studies have shown that the stabilities of p53, MDM2, and MDMX are tightly controlled by the ubiquitin-proteasome system. Ubiquitin specific protease 7 (USP7), one of the most studied deubiquitinating enzymes plays a crucial role in protecting MDM2 and MDMX from ubiquitination-mediated proteasomal degradation. USP7 is overexpressed and constitutively activated in human cancers and contributes to cancer initiation and progression. USP7 inhibition promotes the protein degradation of MDM2 and MDMX, activates the p53 signaling, and causes cell cycle arrest and apoptosis, making USP7 a potential target for cancer therapy. Several small-molecule inhibitors of USP7 have been developed and shown promising efficacy in preclinical settings. In the present review, we focus on recent advances in the understanding of the USP7-MDM2/MDMX-p53 network in human cancers as well as the discovery and development of USP7 inhibitors for cancer therapy.